Uplift capacity of plate anchors: application to transmission poles - Kalaga, Sriram (Journal of Structural Engineering, 2024)
A brief review of current research on uplift or pull-out capacity of plate anchors buried in various types of soils is presented. The definitions of shallow and deep foundations are examined with reference to direct embedded transmission poles. Classical uplift capacity models for plate anchors are discussed. Both cohesion-less (sand) and cohesive (clay) soils are considered. Procedures for computing approximate uplift capacity of transmission poles with base shoes and practical challenges are discussed. Numerical applications involving wood and steel poles embedded in soft clay and loose sand are provided. Results indicate that simplified approaches appear to agree well with classical theory for both the wood and steel poles, though the difference is more noticeable in soft clay.